Health systems and social values: the case of the South African health system - Whyle, Eleanor (Department of Public Health and Family Medicine, 2023)
Health systems are complex social systems – driven by people and the relationships between them, characterised by feedback loops and path-dependency, and open to contextual influences. This entails that social values are an important determinant of health system change. In addition, health systems play a vital social role as generators of social value. However, the influence of social values on health systems is an under-explored field of study, and the evidence-based on the topic is weakened by conceptual confusion, a lack of theoretical models to support rigorous research, a dearth of empirical evidence, and methodological challenges attendant to the study of intangible factors such as values. In this theory-building study I explore the relationship between health systems and social values. Firstly, I use evidence mapping, interpretive synthesis and scoping review approaches to identify gaps in the existing evidence-base, develop an initial explanatory theory for the social value of health systems, and integrate insights from social sciences to establish a working definition of values, explore the social dynamics of values, and develop an account of the relationship between social systems – including health systems – and social values. Secondly, I conduct a case study of social values in the South African National Health Insurance policy process in its social and political context to gather empirical evidence on the role of social values in health system reform processes, and the mechanisms by which health systems shape social values. Lastly, I integrate the findings from the first two phases to develop a conceptual framework of the relationship between health systems and social values and offer methodological and conceptual insights intended to support further research on the topic. This study finds that social values, often borne out of social and political history, are cemented in health systems through daily practices and procedures. In this way, health systems serve to shape social values – by changing the way people think about what is just with respect to healthcare, their health rights and entitlements, and the appropriate role of the state in providing healthcare and regulating the behaviour of other health system actors.